STUDI ANALISIS AYAT-AYAT BULLYING DAN PENGELOLAAN PERILAKU BULLYING - Sri Ramdani, Muhammad Zidan Al-Anshori dan (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2024)
Bullying is an unpleasant act committed by an individual or group of people, either verbally, physically, or socially, both in real life and in the virtual world. In Islam, the practice of bullying has existed since ancient times, as illustrated in the story of Yusuf AS who experienced violence from his brothers, as described in the Quran. This research aims to see and know the interpretation of verses about bullying in the Quran and the solution to bullying behavior according to the Quran. This research uses a literature study using the thematic interpretation method (maudhu'i), which is interpreting the Qur'an by focusing on one particular theme. The verses related to the theme are collected and analyzed, taking into account the semantic aspects and their interpretation. The result of this study is that although the Quran does not directly address bullying, it describes similar acts, especially verbally. The Quran provides solutions such as remembering Allah, speaking kindly, apologizing, and managing words wisely. The importance of implementing these solutions is to create a bullying-free environment.